Hospital responses to COVID-19: evidence from case studies to support future healthcare design research. Issue 1 (3rd November 2021) - Setola, Nicoletta; Naldi, Eletta; Arnetoli, Maria Vittoria; Marzi, Luca; Bologna, Roberto
Abstract : Purpose: The Covid-19 pandemic has placed health-care systems and their facilities throughout the world under immense pressure. The pandemic has highlighted the crucial role of health-care facilities design in looking beyond the ongoing crisis and considering how hospitals can better prepare for unexpected future health situations. This study aims to investigate how hospitals reacted to the crisis in terms of their physical spaces, which architectural features permitted the necessary transformations, and how this data can inform hospital design research in the future. Design/methodology/approach: The research adopted a qualitative and multi-method approach to case studies. Data was collected directly (field survey and interviews) and indirectly (literature, periodicals, specialised websites, webinars, conferences and forums), and a strengths, weaknesses, opportunities, threats analysis supported the data evaluation. Findings: Hospitals' responses to the crisis were guided by a host of variables depending on the specific intervention context and risk scenario. Some key issues emerged as particularly meaningful to drive future research in hospital design, namely, architectural typology, layout and spatial proximities, technological systems, the quality of care spaces, the role of public spaces, facility management tools to drive the transformation, territorial health care networks and new technologies. Originality/value: The paper suggests that the current crisis can be transformed into an opportunity, in terms of research and innovation, to rethink and improve the quality and efficiency of health-care spaces, restoring their crucial role of promoting health by design.